Associations between telomere length and symptoms of posttraumatic stress disorder and appetitive aggression in trauma-exposed men. (19th January 2022) - Womersley, Jacqueline S.; Xulu, Khethelo R.; Sommer, Jessica; Hinsberger, Martina; Kidd, Martin; Elbert, Thomas; Weierstall, Roland; Kaminer, Debbie; Malan-Müller, Stefanie; Seedat, Soraya; M. J. Hemmings, Sian
Highlights: Appetitive aggression and PTSD are associated with exposure to community violence. There is a paucity of data on the neurobiology of appetitive aggression. Telomere length is associated with PTSD and appetitive aggression symptom severity. Trauma may induce homeostatic mechanisms to protect against telomere length attrition. Abstract: Exposure to community violence is common in South Africa and negatively impacts on biopsychosocial health. Posttraumatic stress disorder (PTSD) is characterised by symptoms of intrusion, avoidance, hypervigilance and negative alterations in cognition and mood, and can develop consequent to trauma exposure. Individuals who repeatedly experience and witness violence may also come to view it as appealing and rewarding. This appetitive aggression (AA) increases the likelihood of perpetrating violence. Telomeres are repetitive nucleotide sequences that protect the ends of chromosomes. Telomere length (TL) attrition is a stress-sensitive marker of biological aging that has been associated with a range of psychiatric disorders. This study investigated the cross-sectional relationship between TL and symptoms of PTSD and AA in South African men residing in areas with high community violence. PTSD and AA symptom severity was assessed in 290 men using the Posttraumatic Stress Disorder Symptom Scale – Interview (PSS-I) and Appetitive Aggression Scale (AAS), respectively. Quantitative polymerase chain reaction was performed on DNA extracted from saliva and used to calculate relative TL (rTL). Regression models were used to assess the relationships between rTL and PSS-I and AAS scores. Network analyses using EBIC glasso methods were performed using rTL and items from each of the AAS and PSS-I measures. Both PSS-I (p = 0.023) and AAS (p = 0.016) scores were positively associated with rTL. Network analyses indicated that rTL was weakly related to two PSS-I and five AAS items but performed poorly on indicators of centrality and was not strongly associated with measure items either directly or indirectly. The positive association between rTL and measures of AA and PTSD may be due to the induction of protective homeostatic mechanisms, which reduce TL attrition, following early life trauma exposure.